Gas and star formation from HD and dust emission in a strongly lensed galaxy. Issue 3 (7th September 2020) - Jones, G C; Maiolino, R; Caselli, P; Carniani, S
ABSTRACT: The molecular gas content of high-redshift galaxies is a highly sought-after property. However, H2 is not directly observable in most environments, so its mass is probed through other emission lines (e.g. CO, [C i ], [C ii ]), or through a gas-to-dust ratio. Each of these methods depends on several assumptions, and are best used in parallel. In this work, we extend an additional molecular gas tracer to high-redshift studies by observing hydrogen deuteride (HD) emission in the strongly lensed z = 5.656 galaxy SPT0346−52 with ALMA. While no HD(1–0) emission is detected, we are able to place an upper limit on the gas mass of M_H_26.4× 10^11 M_ . This is used to find a limit on the L^′ _ CO conversion factor of α _CO5.8 M_(K km s^-1 pc^2)^-1 . In addition, we construct the most complete spectral energy distribution of this source to date, and fit it with a single-temperature modified blackbody using the nested sampling code multinest, yielding a best-fitting dust mass Mdust = 10 8.92 ± 0.02 M⊙, dust temperature 78.6 ± 0.5 K, dust emissivity spectral index β = 1.81 ± 0.03, and star formation rate SFR = 3800 ± 100 M⊙ yr −1 . Using the continuum flux densities to estimate the total gas mass of the source, we find M_H_22.4× 10^11 M_ , assuming subsolar metallicity. This implies a CO conversion factor of αCO < 2.2, which is between the standard values for MW-like galaxies and starbursts. These properties confirm that SPT0346−52 is a heavily starbursting, gas-rich galaxy.